2010
DOI: 10.1002/jssc.201000028
|View full text |Cite
|
Sign up to set email alerts
|

Plasma brominated polymer particles as grafting substrate for thiol‐terminated telomers

Abstract: A combined surface activation and "grafting to" strategy was developed to convert divinylbenzene particles into weak cation exchangers suitable for protein separation. The initial activation step was based on plasma modification with bromoform, which rendered the particles amenable to further reaction with nucleophiles by introducing Br to a surface content of 11.2 atom-%, as determined by X-ray photoelectron spectroscopy. Grafting of thiol-terminated glydicyl methacrylate telomers to freshly plasma activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In view of incorporating −SH functions in the material taking advantage of the reactivity of the C–Br bond, a chemical reaction is induced between Br-PPF and propanedithiol. The choice of the grafting reaction is inspired from the study of Byström et al investigating the nucleophilic reaction between the C–Br bond and a thiol-terminated glycidyl methacrylate telomers . It has been demonstrated that the reaction proceeds through the nucleophilic attack on the C–Br bond of the thiol-terminal group of the grafting molecule resulting, in fine, in the formation of the thioether bond (i.e., C–S–C) and the removing of bromine atom in the form of HBr.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of incorporating −SH functions in the material taking advantage of the reactivity of the C–Br bond, a chemical reaction is induced between Br-PPF and propanedithiol. The choice of the grafting reaction is inspired from the study of Byström et al investigating the nucleophilic reaction between the C–Br bond and a thiol-terminated glycidyl methacrylate telomers . It has been demonstrated that the reaction proceeds through the nucleophilic attack on the C–Br bond of the thiol-terminal group of the grafting molecule resulting, in fine, in the formation of the thioether bond (i.e., C–S–C) and the removing of bromine atom in the form of HBr.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of the grafting reaction is inspired from the study of Bystrom et al investigating the nucleophilic reaction between the C−Br bond and a thiol-terminated glycidyl methacrylate telomers. 39 It has been demonstrated that the reaction proceeds through the nucleophilic attack on the C−Br bond of the thiolterminal group of the grafting molecule resulting, in fine, in the formation of the thioether bond (i.e., C−S−C) and the removing of bromine atom in the form of HBr. Because, in this work, the objective is to incorporate −SH terminated groups at the interface, in comparison with the strategy employed by Bystrom et al, a molecule containing an −SH function at each extremity is consequently employed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maleic acid has been applied in the preparation of weak acid cation exchange stationary phase by Schomburg . In this work, carboxylic acid anhydride was selected as the carboxylation reagent to prepare the carboxylic acid‐based cation exchanger .…”
Section: Introductionmentioning
confidence: 99%